The buffalo hunter hunter eaudiobook - Jones, Stephen Graham (Simon & Schuster Audio, 2025)
From the New York Times bestselling author of The Only Good Indians is a chilling historical horror novel tracing the life of a vampire who haunts the fields of the Blackfeet reservation looking for justice. A diary, written in 1912 by a Lutheran Pastor is discovered within a wall. What it unveils is a slow massacre, a chain of events that go back to 217 Blackfeet dead in the snow. Told in transcribed interviews by a Blackfeet named Good Stab, who shares the narrative of his peculiar life over a series of confessional visits. This is an American Indian revenge story written by one of the new masters of horror, Stephen Graham Jones.